Cognitive cerebellum dominates motor cerebellum in functional decline of older adults with mild cognitive impairment - Maria Devita; Alessandra Coin; Chiara Ceolin; Giulia Debiasi; Mariagiulia Anglani; Chiara Begliomini; Simone Cauzzo; Francesca Biasin; Carlo Gabelli; Alessandra Codemo; Michela Sarlo; Marina De Rui; et al. (PLoS ONE, 2025)
Objectives The present study aims to investigate the role that cognitive cerebellar lobules, compared to the motor ones, could have on performance abilities control in older individuals with Mild Cognitive Impairment (MCI). Methods Thirty-six participants with MCI were retrospectively recruited from the outpatient clinic for Cognitive Decline and Dementia at Geriatric Clinic and Regional Center for Brain Aging. Cognition was assessed through a reaction time (RT) task in which a mere cognitive (COG) component (RT/S1 COG, RT/S3 COG) has been isolated from a motor (MOT) component (RT/S1 MOT, RT/S3 MOT). Performance abilities were evaluated using Short Physical Performance Battery (SPPB), Tinetti Scale, and Activities of Daily Living (ADL). Finally, structural neuroimaging was conducted using magnetic resonance imaging at 3T. Results Left_Crus_I showed a correlation with SPPB, ADL%, and RT/S3 COG. Vermis_VI and Right_VI were correlated to ADL%, and RT/S3 COG with the entire lobule VI. ADL% showed negative correlations with RT/S1 COG, RT/S3 COG, and RT/S3 MOT. In the regression analysis, the strongest associations were found between RT/S3 COG and SPPB gait speed (R2 = 0.44, p = 0.03), Tinetti gait speed (R2 = 0.62, p < 0.001), and ADL% (R2 = 0.78, p < 0.001). Regarding cerebellar volumes, Right_Crus_I was associated with all SPPB tests, while Left_VI was associated with functional autonomy (ADL%: R2 = 0.78, p = 0.04). No associations were found between performance variables and total intracranial volume. Conclusions This study highlights that the cognitive cerebellar component dominates over the motor one even in the control of physical and functional capabilities of older adults with MCI.